PENGEMBANGAN MEDIA VIDEO INTERAKTIF BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) MATERI BANGUN DATAR KELAS IV MADRASAH IBTIDAIYAH - Muhammad Najib; Nafa Indah Budi Lestari; Fatonah Salfadilah; Muhamad Supriadi; Futihatul Janah (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2023)
The development of CTL-based interactive video media is motivated by the lack of utilization of media such as videos in the learning process, thus causing a lack of student interest in learning, especially in mathematics subjects. With the use of this media, the learning process becomes more interesting and fun. The purpose of this research is to produce a product in the form of CTL-based interactive video media that is suitable for mathematics subjects on flat building materials. The type of research used is R&D with the 4D model (Define, Design, Development, Dessemination) or called the 4Ps, namely Defining, Planning, Development and Dissemination. This media was validated by media experts and material experts who were then tested on grade 4 Madrasah Ibtidaiyah students totaling 21. The results of the media expert validation obtained an overall average score of 87% with the criteria